Penerapan Latihan William Flexion pada Petani dengan Low Back Pain di Desa Pringanom Kabupaten Sragen - Eka Nikmah Wulandari; Riyani Wulandari (Lembaga Pengembangan Kinerja Dosen, 2024)
Based on the data from Central Java shows that 40% people started from 20 until 65 years old suffered from LBP, estimated 18,2% for men and 13,6% for women. All farmer activities involve the spinal muscles which can caused farmers to suffer from low back pain. One steps to reduce LBP is apply the William Flexion. Describe the results observations application William Flexion to Farmer with Low Back Pain. This method descriptive analysis and a pain measurement scale with Visual Analog Scale (VAS). In this method implemented the William Flexion, measured level Low Back Pain after intervention has been carried out for 6 meetings in 2 weeks. After applying the William Flexion to the respondents, there was a reduction in the level of Low Back Pain. Application William Flexion to farmers with Low Back Pain can reduce level of pain.